PK-2 Pararaft Kit display at the Naval Science Symposium - United States. Navy; Naval Air Engineering Center (U.S.) (1959)
General view of the PK-2 Pararaft Kit display at the Naval Air Engineering Center's Naval Science Symposium. Laboratory Technical Director J. Hartley Bowen, Jr. (right, wearing glasses) is seen explaining the Pararaft Kit, which contains a one-man life raft and other survival accessories, to Dr. Joseph A. Faull (left) of the Office of Naval Research in Boston. Dr. G.K. Holmes, Head of the Naval Air Engineering Center's Chemical Division, stands next to Bowen.
Keywords: Employees; Exhibitions; Trade shows; Survival and emergency equipment; Naval Air Engineering Center (U.S.)